How to design Internet of Things to encourage office workers to take more regular micro-breaks - Huang, Yitong (2016)
Prolonged sitting at work has become a new health hazard for office workers. The current PhD is thus dedicated to exploring the potential of Internet of Things (IoT) for supporting healthier office work and break routines. An "enchanted object" approach that utilizes the "glanceability" and "gesturability" of everyday artefacts is proposed as a potential solution to tackle the challenge of user disturbance and scarcity of cognitive resources in this persuasion context. The vision is to eventually have a collection of digitally "enchanted" office objects that harness ubiquitous sensing and context-aware algorithms to subtly prompt different types of breaks at opportune moments throughout workdays, as a mechanism to break up prolonged sitting; in addition, behavioural data captured from embedded and wearable sensors will be visualized to facilitate self-reflection and habit development. An initial qualitative study is being conducted to unpack challenges and opportunities in reducing prolonged sitting in office work through the lens of both behaviour change and Human Computer Interaction, which has led to preliminary insights to share and discuss with the audience.